AI-Professional Development Model for Chemistry Teacher: Artificial Intelligence in Chemistry Education - Bekir Yildirim; Ahmet Tayfur Akcan (Journal of Education in Science, Environment and Health)
This study aimed to propose a Professional Development Model (PDM) for chemistry teachers to enhance their professional development in Artificial Intelligence (AI). The research group consisted of 17 chemistry teachers. The study was designed using a particular case study suitable for qualitative research methods. Document review, teacher interviews, and AI opinions were utilized to create the model. Data were analyzed using inductive content analysis. The document analysis emphasized the teachers' knowledge of various topics, such as AI knowledge, AI tools, AI skills, AI ethics, AI attitudes, and AI literacy, to enable them to incorporate AI into their lessons. It was also highlighted that teachers should acquire domain-specific knowledge, skills, and competencies in the areas where artificial intelligence will be integrated. When examining the recommendations of artificial intelligence (ChatGPT and Gemini), it was found that they addressed similar content to the information included in the document analysis. Furthermore, chemistry teachers stated their deficiencies in AI literacy, AI competencies, and developing AI lesson plans. They also stated that AI applications could be included in various subjects such as organic chemistry, chemical experiments, and chemical reactions. Following the analysis of documents and teacher and AI opinions, a 10-step PDM has been proposed to enhance chemistry teachers' professional development in AI.